FORMULATION, EVALUATION, AND IN VIVO ANTI-INFLAMMATORY AND ANTI-ARTHRITIC ACTIVITIES OF MORINGA GRANULES - ALSAMMARRAIE, HARITH JAMEEL MAHDI; KHAN, NURZALINA ABDUL KARIM; MAHMUD, ROZIAHANIM (International Journal of Applied Pharmaceutics, 2021)
Objective: Consumption of crude natural products like plants and herbs for mitigation or treatment of illnesses usually accompanied with inconsistent therapeutic effects because of poor solubility and low bioavailability of active phytochemical(s) in addition to product instability. To overcome all of above mentioned drawback ethanol extract of Moringa oleifera leaf was formulated as standardised solid dosage form. Methods: Different types of materials as an adsorbent, surfactant and other necessary excipients were tested to be use in formulation of Moringa granules utilising wet granulation method. The formulated Moringa granules was then evaluated for organoleptic properties and physical characteristics, in vitro dissolution test, compatibility, drug content, heavy metal tests and microbial limit tests. Additionally, the in vivo anti-inflammatory against Carrageenan-induced paw oedema and anti-arthritic activity against CFA-induced arthritis were also assessed. Results: 95% ethanol extract of M. oleifera leaves was successfully formulated as standardised granules for oral administration utilising simple and low-cost techniques. Dissolution rate for the marker compounds was increased by an average of 1.076 fold. Animal groups given the prepared Moringa granules showed an improvement in the anti-inflammatory activity and the anti-arthritic activity compared to animal groups given crude extract at the same dose level. Additionally, all the treatment groups showed a significant difference at P<0.05 and P<0.01 compared to control group. Conclusion: To the best of our knowledge, this work was the first to use gum Arabic in the formulation of a standardised botanical pharmaceutical dosage form of M. oleifera crude extract. Additionally, formulation of Moringa granules apparently improves the drug release profile and bioactivity compare to Crude Moringa extract.